Aplikasi Teori Cheryl T Beck dalam Asuhan Keperawatan pada Kasus Depresi Post Partum - Khaier, Nurhayati; Nursanti, Irna (Jurnal Sains, Teknologi dan Kesehatan, 2024)
This study explores postpartum depression using the Beck theory. Factors such as anxiety, stress, and breastfeeding difficulties form the framework of analysis. Applied nursing care includes clinical evaluation, understanding thought patterns, therapeutic relationship development, education, and cognitive interventions. While the Beck theory focuses on cognitive aspects, there are weaknesses such as generalization and a lack of attention to social, environmental, and biological aspects.